The interhemispheric and F region dynamo currents revisited with the Swarm constellation. Issue 9 (4th May 2015) - Lühr, Hermann; Kervalishvili, Guram; Michaelis, Ingo; Rauberg, Jan; Ritter, Patricia; Park, Jaeheung; Merayo, Jose M. G.; Brauer, Peter
Abstract Based on magnetic field data sampled by the Swarm satellite constellation it is possible for the first time to determine uniquely F region currents at low latitudes. Initial results are presented from the first 200 days of formation flight (17 April to 5 November 2014). Detailed results have been obtained for interhemispheric field‐aligned currents connecting the solar quiet day magnetic variation (Sq) current systems in the two hemispheres. We obtain prominent currents from the Southern (winter) Hemisphere to the Northern around noon. Weaker currents in opposite direction are observed during morning and evening hours. Furthermore, we could confirm the existence of vertical currents above the dip equator, downward around noon and upward around sunset. For both current systems we present and discuss longitudinal variations.